Traditions and innovations in the study of Middle English literature : the influence of Derek Brewer - Brewer, Charlotte, 1956-; Windeatt, B. A. (Barry A.), 1950-; Brewer, Derek, 1923-2008 (D.S. Brewer, 2013)
"Derek Brewer (1923-2008) was one of the most influential medievalists of the twentieth century, first through his own publications and teaching, and later as the founder of his own academic publishing firm. His working life of some sixty years, from the late 1940s to the 2000s, saw enormous advances in the study of Chaucer and of Arthurian romance, and of medieval literature more generally. He was in the forefront of such changes, and his understandings of Chaucer and of Malory remain at the core of the modern critical mainstream. Essays in this collection take their starting point from his ideas and interests, before offering their own fresh thinking in those key areas of medieval studies in which he pioneered innovations which remain central: Chaucer's knight and knightly virtues; class-distinction; narrators and narrative time; lovers and loving in medieval romance; ideals of feminine beauty; love, friendship and masculinities; medieval laughter; symbolic stories, the nature of romance, and the ends of storytelling; the wholeness of Malory's Morte Darthur; modern study of the medieval material book; Chaucer's poetic language and modern dictionaries; and Chaucerian afterlives. This collection builds towards an intellectual profile of a modern medievalist, cumulatively registering how the potential of Derek Brewer's work is being reinterpreted and is renewing itself now and into the future of medieval studies"--Provided by publisher.